The impact of the environment and community habits on malaria knowlesi post-elimination of malaria in UPTD Puskesmas Jaboi's work area in Sabang City - Aditama, Wiwit; Zulfikar; Maulidin, Ichsan (Universitas Gadjah Mada, 2023)
Purpose: Malaria has spread to over 100 countries with tropical and subtropical climates globally. Around 35% of the population in Indonesia lives in areas at risk of malaria infection, and 38 thousand people die each year from severe malaria caused by Plasmodium falciparum. Malaria outbreaks occur almost annually in Indonesia's various endemic areas. The purpose of this study was to ascertain Malaria Knowledge following Malaria Elimination in the Jaboi Health Center's UPTD Work Area in Sabang City. Methods: This research is descriptive by design Case-Control. The number of samples in this study was 7 people and 23 people as controls with chi-square test analysis. Results: According to the study's findings, there was a relationship between four broods and malaria (P = 0.014), no relationship between the habit of going out at night (P = 0.190), and a relationship between the use of repellents (0.009) and malaria following malaria elimination in the work area of UPTD Puskesmas. Jaboi, post-elimination cases of malaria knowlesi continue to occur due to an environment that is still conducive to mosquito breeding sites and as a result of the population's geographical location in an area with a high concentration of wild animals. Conclusion: There is a correlation between breeding sites and repellent use and malaria in the work area of the Jaboi Health Center UPTD Sabang City, but there is no correlation between the habit of going out at night and malaria in the work area of the Jaboi Health Center UPTD Sabang City.